Highly branched isoprenoids in lake photic zone water - Aaron F Diefendorf; Watts Dietrich; Hans H Naake; Thomas V Lowell; Megan C Corcoran (PANGAEA, 2025)
Diatom-derived highly branched isoprenoids (HBIs) are found extensively in marine sediments, but are observed in a limited number of lake sediments. To expand on this record, between 2022 and 2024, we collected lake surface sediment samples from 50 lakes in the United States of America from the Midwest and Northeast. Studied lakes capture a range in climate, water chemistry (e.g., pH, salinity, alkalinity), size, and trophic states. Lakes also vary in their diatom species compositions. Water samples from the photic zone were collected using an integrated water sampler. The integrated sample was designed to collect the water from the euphotic zone where phytoplankton are concentrated. Water was sampled from the euphotic zone (calculated as 2 times the Secchi disk depth) using an integrated water sampler fabricated from a 2 m long x 5.2 cm ID PVC pipe (2" nominal schedule 40 PVC pipe) fitted with a ball valve at the top. When the euphotic zone was >2 m, only the upper 2 m was sampled. When the euphotic zone intersected with the sediment/water interface, water was collected from the surface to 0.5 m above the sediment/water interface. Waters were filtered first through 1000 μm mesh filter and then onto a 0.7 μm glass fiber filter. Filters were extracted and analyzed by gas chromatography mass spectrometry.
In: Diefendorf, AF et al. (2025): Diatom-derived highly branched isoprenoids in lake waters and sediments [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979496